Rhizobia in tropical legumes—IX. pot and field trials with inoculants for Psophocarpus tetragonolobus (L.) DC. - Ikram, A.; Broughton, W.J. (1980)
Antigenically identifiable inoculants for Psophocarpus tetragonolobus were evaluated in three non-sterile soils contained in pots (sandy-clay, Renggam series; a loamy-sand, Sungei Buloh series; silty-clay, Munchong series). Most-probable-numbers of indigenous rhizobia ranged from 4 (Renggam series) to 13 (Munchong series) g−1. Only two (RRIM 56 and 968) of the eight rhizobia tested formed > 50% of the nodules in all soils. Recovery of two strains (RRIM 968 and UMKL 12) was significantly poorer from the Munchong series soil which had the most indigenous rhizobia and the highest silt plus clay content. In a field trial using a Sungei Buloh series soil containing 700 rhizobia g−1 capable of nodulating P. tetragonolobus, none of the applied strains formed > 18% of the nodules; two formed no nodules. There were no significant increases in plant yield in response to inoculation in the field trial and in two soils in the pot trials. In Sungei Buloh series soil, RRIM 56 formed 90% of the nodules when the indigenous rhizobia were 5 cells g−, and 14% when the population was 700 g−1. This raises the question of the need to inoculate seed sown into soils with high indigenous rhizobial populations, but there was some indication of increasing representation of inoculant strains in nodules with time.